2015
DOI: 10.1039/c5cc04589d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium- and palladium-catalyzed consecutive coupling and cyclization of aromatic sulfoximines with phenylboronic acids: an efficient route to dibenzothiazines

Abstract: A ruthenium-catalyzed ortho arylation of aromatic sulfoximines with aromatic boronic acids followed by intramolecular cyclization in the presence of a palladium catalyst, providing dibenzothiazine derivatives in two consecutive steps, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Synthetic procedures to construct tricyclic dibenzothiazine derivatives are very limited. In 2015, Jeganmohan and co-workers described a two-step procedure to synthesize dibenzothiazine derivatives through ortho arylation of sulfoximines with aromatic boronic acids and subsequent intramolecular cyclization . Later on, a cascade ortho halogenation/Suzuki coupling/oxidative annulation procedure to synthesize dibenzothiazines from N -acylsulfoximines was investigated by the group of Bolm .…”
mentioning
confidence: 99%
“…Synthetic procedures to construct tricyclic dibenzothiazine derivatives are very limited. In 2015, Jeganmohan and co-workers described a two-step procedure to synthesize dibenzothiazine derivatives through ortho arylation of sulfoximines with aromatic boronic acids and subsequent intramolecular cyclization . Later on, a cascade ortho halogenation/Suzuki coupling/oxidative annulation procedure to synthesize dibenzothiazines from N -acylsulfoximines was investigated by the group of Bolm .…”
mentioning
confidence: 99%
“…After the pioneering work on rhodium‐catalyzed oxidative annulation of sulfoximines and alkynes from Bolm and co‐workers, several groups have expanded the coupling partners of sulfoximines to diazo compounds, olefins, pyridotriazoles, 3‐diazoindolin‐2‐imines, α‐MsO/TsO ketones, sulfoxonium ylides, etc . Furthermore, inspired by the well established Rh III catalytic system, several other transition‐metals, including Ru II , Cp*Co III , and Cp*Ir III , have been successfully applied to direct C−H functionalization of sulfoximines. However, to the best of our knowledge, direct alkynylation of C−H bonds of sulfoximines has never been reported and remains as a challenge.…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, Jeganmohan and co‐workers devised an expeditious strategy for the selective ortho C−H arylation of aryl sulfoximine by ruthenium catalysis using arylboronic acids as arylating candidates and consecutive intramolecular cyclization in two steps to afford tricyclic dibenzothiazines 76 in the presence of palladium (II) salt (Scheme 99). [108] Careful screening conditions suggested that the use of 10 mol % [RuCl 2 ( p‐cymene )] 2 , 40 mol % of AgSbF 6 and 1 equiv. of Ag 2 O in THF at 100 °C for 16 h was optimal to achieve a fine conversion of the bis‐arylated products 75 .…”
Section: C−h Functionalizationsmentioning
confidence: 99%